Profesionalni razvoj učiteljev športne vzgoje - Tul, Miloš (Šport (Ljubljana), 2017)
In the present society, which has been often described as a knowledge society, teachers play an important role, hence they are required to possess different skills and competencies to those in the past. Europe has adopted the Lisbon strategy and two European programmes Education & Training 2010 and Education & Training 2020 as a collective response to challenges presented by globalisation, demographic changes and the creation of knowledge society. Both programmes were relatively successful, their most visible result being the transformation of educational programmes for teaching profession. European educational programmes should be directed from the paradigm of a teacher who taught towards the direction of a teacher who encourages and facilitates learning in students with the use of innovative methods and resources. Applying the project AEHESIS as a starting point, most of the European countries changed the physical education teacher education programmes. The researchers in the field of physical education point out that the openness to creation of interesting programmes and innovation in the teaching process, appropriate differentiation of goals according to the characteristics and abilities of the students, and the integration of new teaching technologies are important qualities of modern physical education teachers and their professionalization. It could be concluded that the qualifications acquired during the studying process are no longer sufficient for a quality work in practice. Such understanding forced the governments to focus their efforts on a constant improvement of professional competences, which necessitates a well-formed system of continuing professional development available to all teachers.
Keywords: continuing professional development; educational programmes; izobraževalni programi; physical eduction teacher; profesionalizacija; profesionalni razvoj; professionalization; sport; stalno strokovno spopolnjevanje; šport; učitelji športne vzgoje